Optimized in vitro seed culture for disease-free propagation of curry leaf (Murraya koenigii) - Premasiri, W.M.A.C.; Fonseka, D.L.C.K.; Terensan, S.; Nanayakkara, N. (University of Ruhuna, 2025)
Curry leaf (Murraya koenigii) is a valuable plant in both culinary and medicinal uses, preliminary due to its unique aroma, flavour, and bioactive compounds. This semi-hardwood species in tropical and subtropical regions, however conventional propagation is hindered by bacterial, fungal, and viral infections. These pathogens reduce yield and disrupt genetic fidelity, leading to desirable traits such as aroma, disease resistance, and overall vigor. Although, seed propagation, preferable to vegetative methods, it remains susceptible to contamination. In vitro seed culture presents a viable solution by enabling seed sterilization. Cultivation in a controlled, aseptic environment, thereby eliminating external and some internal contaminants. This approach supports the propagation of disease-free, true-to-type seedlings, and helps conserve elite genotypes. Thus, developing a standardized in vitro seed culture protocol, seeds were collected from fully ripened berries of premium, export-grade curry leaf plants in Jaffna. A total of 108 replicates were used to conduct this research, following 10% and 15% Clorox concentrations with three different exposure times: 10, 15, and 20 minutes. The most effective treatment was identified as 15% Clorox for 20 minutes, yielding the highest survival and contamination-free rate of 78% (P < 0.05). Germinated seedlings were then cultured for shoot proliferation under various hormonal treatments, including 2.0 mg/L, 2.5 mg/L, and 3.0 mg/L 6-Benzylaminopurine (BAP) with 0.5 mg/L Naphthaleneacetic acid (NAA). Among them, 2.5 mg/L BAP with 0.5 mg/L NAA produced the maximum number of shoots per explant, 6 after ten weeks, significantly outperforming other treatments (P < 0.05). These findings, validated through SAS software using ANOVA and Duncan Multiple Range Test (DMRT) analysis, demonstrate that in vitro seed culture with optimized protocols enables large-scale propagation of genetically stable, disease-free curry leaf plants, boosting both commercial viability and export potential.
Keywords: Curry leaf; Murraya koenigii; In vitro propagation; Seeds sterilization; Shoot proliferation